Peer review of the pesticide risk assessment of the active substance abamectin. (30th August 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Austria and co‐rapporteur Member State Malta for the pesticide active substance abamectin are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative uses of abamectin as an insecticide and acaricide on tomato and strawberry, and updated following the request from Commission to review the exposure and risk assessments as regards birds and mammals, aquatic organisms and soil macroorganisms. The risk assessment to bees and non‐target arthropods was also updated. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.